An Overview of Patient Safety Supervision in Government Hospitals - Apriando Rahmadani; Yulastri Arif; Rian Ferdian (Indonesian Journal of Global Health Research, 2025)
Effective supervision is needed to achieve optimal implementation of patient safety goals, where patient safety is prioritized in every activity. Nurses' performance in implementing patient safety goals is influenced by several factors. Objective to know the description of patient safety supervision in hospitals in 2024. This study is a quantitative study with a cross-sectional design conducted in April-June 2024 at the Hospital. The study population was all executive nurses in the hospital inpatient room. The population was 42 people with total sampling technique. The research instrument used a questionnaire to collect data on the characteristics of respondents consisting of nurse identity, namely: level of education, length of work, and supervision. Patient safety supervision is mostly in the good category (78.57%). Patient safety supervision in hospitals in 2024 is mostly in the good category. This indicates that nurses have implemented various safety standards and effective procedures to protect patients from injury or harm during treatment.